PERANCANGAN KEMASAN TAKE AWAY BUBUR AYAM MENGGUNAKAN METODE QUALITY FUNCTION DEPLOYMENT (QFD) - M Zulfan Rizaldi; Lina Dianati Fathimahhayati; Farida Djumiati Sitania (Journal of Industrial and Engineering System, 2020)
The development of the culinary business in Indonesia is currently quite rapid. One effort that can be done in the face of fierce product competition is through packaging design. The packaging used to package is not attractive because it is in the form of packaging with ordinary Styrofoam (PS or Polystyrene). Besides, the packaging is easily damaged in the lock and cannot be tightly closed, making it difficult for consumers when they want to consume porridge while on the way and do not have a clear identity to represent the brand of Kabayan Chicken Porridge. This study aims to provide recommendations for designing Kabayan Chicken Porridge packaging using the Quality Function Deployment (QFD) method. Data processing uses the product planning stage by preparing the House of Quality (HOQ) and the design deployment stage. After processing the data in the two stages of Quality Function Deployment (QFD), 24 critical parts were used as a reference in the design of Kabayan Chicken Porridge Take Away packaging. The recommended recommendations are paper bowl packaging which is waterproof, easily distributed, uses attractive fonts, uses attractive colors and does not conflict with product characteristics, uses easy-to-open and closed lid covers, displays product photos, displays manufacturer information, and displays the logo.